Validity and Practicality of Sangiran Site-Based Virtual Laboratory Learning Media on Evolutionary Materials to Empower Science Literacy - Wahyu Pangestuning Astuti; Murni Ramli; Suranto Suranto (Postgraduate, University of Mataram, 2022)
The validity and practicality of the media are a condition before it can be widely piloted. This research aims to find out the validity and practicality of the Evolution Virtual Laboratory Learning Media, which was developed based on the artefacts of the Sangiran Site to empower science literacy of students. The media validity test using expert judgment involved two expert validators, and two high school biology teachers. While the media practicality test involved 20 grade 12th students. The instrument used was a validity questionnaire consisting of 9 items (material experts), 18 items (media experts), and 13 items (practitioners). Questionnaire instruments to students as many as 16 items. All questionnaires use the Likert Scale. The test results showed material experts rated 86.80%, media experts 84.6%, education practitioners 84.30%, and students by 79.00%. Based on the validity and practicality of the Sangiran Site-based Evolution virtual laboratory learning media is declared valid and practical, so it can be used for effectiveness testing.